2003
DOI: 10.1063/1.1568931
|View full text |Cite
|
Sign up to set email alerts
|

A surface forces platform for dielectric measurements

Abstract: Articles you may be interested in Dielectric relaxation in ionic liquids: Role of ion-ion and ion-dipole interactions, and effects of heterogeneity J. Chem. Phys. 140, 014504 (2014) Methods are described to implement dielectric spectroscopy ͑frequency range 10 Ϫ1 -10 6 Hz) within a surface forces apparatus by using as electrodes silver sheets on the backside of mica. These methods are applied to study the competitive effects of surface alignment, confinement, and shear field on 5CB ͑5-cyanobiphenyl͒, a nematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…The alignment of LC itself involves complex physicochemical interactions between the LC molecules and the alignment film. It was found that the homeotropic alignment of LC is caused by the weak anchoring [16] and is favoured when the surface is hydrophobic [12].…”
Section: Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The alignment of LC itself involves complex physicochemical interactions between the LC molecules and the alignment film. It was found that the homeotropic alignment of LC is caused by the weak anchoring [16] and is favoured when the surface is hydrophobic [12].…”
Section: Wettabilitymentioning
confidence: 99%
“…It is in the nematic phase between 14.5 and 29 • C. Its physical properties have been studied extensively. The dielectric anisotropy is positive because the dipole moment of the cyano group in the molecule is nearly parallel to the long molecular axis [12]. The LC material was syringed into a d = 20 µm thick symmetric cell with Mylar spacers between the two functionalized ITO substrates.…”
Section: Nlc Cell Constructionmentioning
confidence: 99%
“…Hence, vertical orientation of LC is much more favorable on an alignment layer with low surface energy. [6,7] Now we need to explain this phenomenon in more detail because the alignment of LC is induced by complex physicochemical interactions between the LC molecules and the aligned films. To explain the orientational recovery to VA, several types of interactions must be considered, including p-p electron coupling, geometric effect, dipole-dipole interaction, and van der Waals interaction.…”
mentioning
confidence: 99%
“…Usually the homeotropic alignment of LCs is realized by the hydrophobic surface if there is no preferential orientation or surface roughness. [6,7] One way to achieve such alignment of LCs is to adsorb a surfactant monolayer on the surface to render it hydrophobic. [8,9] Geometrical factors can also be responsible; for example, LC molecules align parallel to the flexible long chains of a surfactant attached to substrate surfaces perpendicularly.…”
mentioning
confidence: 99%
“…To analyze the degradation with time, we fabricated an ion-doped LC cell and measured the haze and impedance. Impedance and dielectric spectroscopic analyses were carried out to extract the impedance parameters, such as the resistance and capacitance of the LCs and physical parameters of the ionic materials in the bulk regions and near the alignment layers [29][30][31][32][33][34][35]. With the increase in time under the applied electric field, the LC cell exhibited nonuniformity with the decrease of the haze, capacitance of the LC cell, and thickness of the diffusion layer, along with the increase of the resistance of the LC cell and surface concentration of the ions.…”
Section: Introductionmentioning
confidence: 99%